Thermal Cooling of Solar Panels: Effectiveness of Copper Pipes in Temperature Regulation - Ramadhan, Hanif; Jamaaluddin, Jamaaluddin; Ahfas, Akhmad; Anshory, Izza (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2025)
This study evaluates the effectiveness of a thermal cooling system utilizing copper pipes in regulating solar panel temperature and enhancing energy efficiency. The system incorporates water-fed copper pipes with an automatic valve mechanism, which controls water flow based on real-time temperature measurements. Experiments were conducted at Universitas Muhammadiyah Sidoarjo using two 100 Wp solar panels, where key parameters such as voltage, current, power output, and surface temperature were monitored. The results demonstrate that the cooling system effectively lowers panel temperature, leading to significant improvements in voltage and power generation. The cooled solar panel achieved a maximum efficiency of 43.7%, compared to only 24.07% without cooling. Additionally, the cooling system stabilized maximum power voltage (VMP) and maximum power output (PMAX), preventing performance degradation due to excessive heat accumulation. These findings confirm that integrating a copper pipe thermal cooling system enhances solar panel efficiency, providing a viable solution for improving photovoltaic energy conversion and ensuring long-term operational stability.